Direct patient costs of maternal care and birth-related complications at faith-based hospitals in Madagascar: a secondary analysis of programme data using patient invoices - Franke, Mara Anna; Ranaivoson, Rinja Mitolotra; Rebaliha, Mahery; Rasoarimanana, Sahondra; Bärnighausen, Till; Knauss, Samuel; Emmrich, Julius (BMJ open, 2022)
Objectives We aimed to determine the rate of catastrophic health expenditure incurred by women using maternal healthcare services at faith-based hospitals in Madagascar. - Design This was a secondary analysis of programmatic data obtained from a non-governmental organisation. - Setting Two faith-based, secondary-level hospitals located in rural communities in southern Madagascar. - Participants All women using maternal healthcare services at the study hospitals between 1 March 2019 and 7 September 2020 were included (n=957 women). - Measures We collected patient invoices and medical records of all participants. We then calculated the rate of catastrophic health expenditure relative to 10% and 25% of average annual household consumption in the study region. - Results Overall, we found a high rate of catastrophic health expenditure (10% threshold: 486/890, 54.6%; 25% threshold: 366/890, 41.1%). Almost all women who required surgical care, most commonly a caesarean section, incurred catastrophic health expenditure (10% threshold: 279/280, 99.6%; 25% threshold: 279/280, 99.6%). The rate of catastrophic health expenditure among women delivering spontaneously was 5.7% (14/247; 10% threshold). - Conclusions Our findings suggest that direct patient costs of managing pregnancy and birth-related complications at faith-based hospitals are likely to cause catastrophic health expenditure. Financial risk protection strategies for reducing out-of-pocket payments for maternal healthcare should include faith-based hospitals to improve health-seeking behaviour and ultimately achieve universal health coverage in Madagascar.